Efektivitas Penggunaan Model Project Based Learning Berbasis STEM Pada Materi Fluida Statis untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi Peserta Didik di Kelas XI MIA SMA Negeri 8 Ambon - Radja Udju, Delans Fabiyolla Putri; Limba, Anatasija; Tamaela, Elsina (Pattimura University, 2023)
This study aims to determine the effectiveness of using the STEM-project based learning model to improve students' high-level thinking skills in learning static fluid material in class XI MIA SMA Negeri 8 Ambon. This type of research is quantitative with the research design One Group Pretest-Posttest Design. The subjects in this study were 17 class XI MIA students at SMA Negeri 8 Ambon. Research data were collected using test and non-test instruments (LKPD and response questionnaires). The results of the analysis show that the ability to think at a higher level before using the STEM-PjBL model is less qualified with an average achievement score of 25.3. After using the STEM-PjBL model, the qualifications were good with an average achievement score of 74.9. An increase in higher order thinking skills is obtained by normalizing the gain of 0.7 which is in the high qualification. Testing the effectiveness of using the Paired Sample T-Test showed that there was a difference in the average high-level thinking skills of students before and after using the STEM-PjBL model with a Sig. (2-tailed) is 0.000, this means that the value is 0.000 <0.05, so it can be concluded that the STEM-PjBL model is effective for improving the high-level thinking skills of class XI MIA students in static fluid material